Analisis Dampak Perubahan Ketentuan Tanggung Jawab Direksi dan Pemegang Saham serta Jaminan Perlindungan Hukum bagi Kreditur dan Pihak Ketiga dalam konteks UU Cipta Kerja - Artikasari Artikasari; Marcha Jeanne Mawene; Nabilah Liztha Maharani; Naumy Syauqina Dalida; Sulastri Sulastri (Journal of Student Research, 2025)
This research aims to analyze the impact of changes to the provisions on the responsibilities of directors and shareholders as well as guarantees of legal protection for creditors and third parties in the context of the Job Creation Law. The research method used is normative legal analysis, relying on a study of statutory regulations, relevant legal theories, and selected scientific literature. This normative approach is carried out through in-depth study and interpretation of applicable legal provisions, especially changes regulated in the Job Creation Law. The analysis focuses on how these changes affect the legal responsibilities of directors and shareholders, as well as their impact on the rights of creditors and third parties. Legal theory is used to build a strong conceptual and analytical framework in understanding the legal phenomena that arise from the implementation of this new regulation. It is hoped that the research results will provide a comprehensive understanding of the legal implications of these policy changes, as well as offer recommendations to increase legal certainty for all relevant parties. Thus, it is hoped that this research can be a significant contribution to the development of corporate law studies and legal protection in Indonesia.